Sirtuin‐6 deficiency exacerbates diabetes‐induced impairment of wound healing. Issue 10 (18th August 2015) - Thandavarayan, Rajarajan A.; Garikipati, Venkata Naga Srikanth; Joladarashi, Darukeshwara; Suresh Babu, Sahana; Jeyabal, Prince; Verma, Suresh K.; Mackie, Alexander R.; Khan, Mohsin; Arumugam, Somasundaram; Watanabe, Kenichi; Kishore, Raj; Krishnamurthy, Prasanna
Abstract Delayed wound healing is one of the major complications in diabetes and is characterized by chronic proinflammatory response, and abnormalities in angiogenesis and collagen deposition. Sirtuin family proteins regulate numerous pathophysiological processes, including those involved in promotion of longevity, DNA repair, glycolysis and inflammation. However, the role of sirtuin 6 (SIRT6), a NAD+‐dependent nuclear deacetylase, in wound healing specifically under diabetic condition remains unclear. To analyse the role of SIRT6 in cutaneous wound healing, paired 6‐mm stented wound was created in diabetic db/db mice and injected siRNA against SIRT6 in the wound margins (transfection agent alone and nonsense siRNA served as controls). Wound time to closure was assessed by digital planimetry, and wounds were harvested for histology, immunohistochemistry and Western blotting. SIRT6‐siRNA‐treated diabetic wound showed impaired healing, which was associated with reduced capillary density (CD31‐staining vessels) when compared to control treatment. Interestingly, SIRT6 deficiency decreased vascular endothelial growth factor expression and proliferation markers in the wounds. Furthermore, SIRT6 ablation in diabetic wound promotes nuclear factor‐κB (NF‐κB) activation resulting in increased expression of proinflammatory markers (intercellular adhesion molecule‐1, vascular cell adhesion molecule‐1, tumor necrosis factor‐α and interleukin‐1β) and increased oxidative stress. Collectively, our findings demonstrate that loss of SIRT6 in cutaneous wound aggravates proinflammatory response by increasing NF‐κB activation, oxidative stress and decrease in angiogenesis in the diabetic mice. Based on these findings, we speculate that the activation of SIRT6 signalling might be a potential therapeutic approach for promoting wound healing in diabetics.